A carbon monoxide gas sensor using oxygen plasma modified carbon nanotubes - Yan, Qingyu (2013)
Carbon monoxide (CO) is a highly toxic gas that can be commonly found in many places. However, it is not easily detected by human olfaction due to its colorless and odorless nature. Therefore, highly sensitive sensors need to be developed for this purpose. Carbon nanotubes (CNTs) have an immense potential in gas sensing. However, CNT-based gas sensors for sensing CO are seldom reported due to the lack of reactivity between CO and CNTs. In this work, O2 plasma modified CNT was used to fabricate a CNT gas sensor. The plasma treated CNTs showed selectively towards CO, with the capability of sensing low concentrations of CO (5 ppm) at room temperature, while the pristine CNTs showed no response. UV spectra and oxygen reduction reaction provided evidence that the difference in sensing property was due to the elimination of metallic CNTs and enhancement of the oxygen reduction property.